PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING TIPE TEAMS-GAMES-TOURNAMENT (TGT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN DURIAN TARUNG PADANG - Merryanti, Vina; Aima, Zulfitri; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
Background of this research is the low of student`s comprehension of mathematical concepts and student`s responsible to their exercises that given by the teacher. The purpose of this research is to know what is student`s comprehension of mathematical concepts at grade VIII MTsN Durian Tarung Padang that use cooperative learning model type Teams-Games-Tournament (TGT) better than convensional model. Kind of this research is experimental research, with research plan is Randomized Control Group Only Design. Population of this research is student`s at grade VIII MTsN Durian Tarung Padang academic year 2012/2013. Sample is grade VIII1 as experiment class and VIII2 as control class. The instrumentation of this research is comprehension test of mathematical concept. The form of test is essay with reliabilitastes is r11= 0,77. Technique of data analysis is used in this research is t-test one side by using software minitab. Based on the result of t-test is P-value = 0,001, it means lower than Â = 0,05, therefore hipotesis is accepted furthermove. We can conclude that student`s comprehension of mathematical concept is treated by using cooperative learning model type Teams-Games-Tournament (TGT) better than student`s comprehension of mathematical concept is treated by using convensional learning at grade VIII MTsN Durian Tarung Padang academic year 2012/2013.